The problems of formation for schoolchildren the cognitive interest to music lessons (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the types of pedagogical skills and habits which help the future teachers to form for is hoolchildren the cognitive interest to music lessons.
Keywords: cognitive interests; cognitive activities; musical skills